A novel methodology for imaging newly bone formation around bioceramic bone substitutes - Gorustovich Alonso, Alejandro Adrian (2006)
In this study, Frost's bulk‐staining in combination with confocal laser scanning microscopy (CLSM) was used to image and characterize ground sections of undecalcified rat bone tissue with in situ bioceramic implants. This was addressed by bulk staining specimens in alcohol‐soluble basic fuchsin dye. The ground sections were imaged using CLSM in the confocal fluorescence mode. Confocal images revealed that the newly formed bone could be clearly distinguished from bone marrow and cortical bone, as well as from the implant material.